(untitled) (Global Journal of Medical Research, 2020)
It had pointed out that modern people have a weakening ability to bite. The media had reported that the number of children with weak chewing power has increased since the 1980s, and the media were concerned about their future health. Therefore, in this study, we conducted a questionnaire survey after chewing ability training after chewing gum once a day for one month for chewing ability training. As a result, 23 female university students participated, and after 30 days, six people answered that they got chewing ability by chewing gum everyday. Also, eight people answered that they felt that their jaw had strengthened. And five of the participants answered that saliva secretion had improved. Six of the participants replied that they had reduced their snack intake. However, of the 23 participants, eight could not chew the gum daily for 30 days. Also, 13 out of 23 of the participants replied that chewing gum every day for 30 days was hard to do. In the future, we would like to enlighten people to develop chewing ability training by making a habit of chewing gum everyday.